2010
DOI: 10.1590/s0102-86502010000400006
|View full text |Cite
|
Sign up to set email alerts
|

Porcine peritoneum as source of biocompatible collagen in mice

Abstract: Purpose:To investigate the biocompatibility and biodegradability of a membrane made from porcine peritoneum. Methods: The membrane (5x5 mm) was inserted in the subcutaneous tissue on the back of 15 mice, which were killed after 1, 3 and 9 weeks (ISO 10993-6). The cellular components of the inflammatory response and degradation of the membrane were analyzed in hematoxylin-eosin-stained histological sections. Results: After one week, mononuclear cells were observed inside the membrane. After three weeks, the mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
(12 reference statements)
0
7
0
1
Order By: Relevance
“…Collagen is accepted as a safe material and also has a nontoxic degradation product [4–6]. However, its degradation period is uncontrolled, with a minimum period of 2 weeks and maximum of 8 months after implantation.…”
Section: Introductionmentioning
confidence: 99%
“…Collagen is accepted as a safe material and also has a nontoxic degradation product [4–6]. However, its degradation period is uncontrolled, with a minimum period of 2 weeks and maximum of 8 months after implantation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, collagen has a chemotactic effect on fibroblasts, promoting tissue integration (9). Collagen-based barrier membranes have already been extensively investigated in both animal experiments and clinical studies (3,(14)(15)(16)(17)(18)(19). Although the clinical results related to collagen-based membranes are comparable to those of non-resorbable membranes, their application has a lower incidence of spontaneous exposures (20,21).…”
mentioning
confidence: 99%
“…There are few reports of polymeric biomaterials that maintain their integrity for 30 days or longer in murine subcutaneous tissue [37,38], although partial or total degradation occurs within 21 days [39,40] or even in 7 days [41]. In this study, the presence of the CGP/PVA membrane was observed within 60 days of implantation.…”
Section: Discussionmentioning
confidence: 56%